Mirizzi Syndrome: From Ultrasound Diagnosis to Surgery—A Case Report - Pariani, Dario (Hindawi Publishing Corporation, 2013)
The Mirizzi syndrome is a rare disorder that usually presents with jaundice and cholangitis; its lack of recognition in the diagnostic path could have serious consequences for the patient undergoing cholecystectomy. Here we describe the clinical case of a jaundiced patient from the ultrasound suspect of Mirizzi syndrome to the surgical treatment.